Brief Notes: Logarithmic Screw Dislocation - Wesołowski, Z. (Engineering Transactions, 2004)
Basing on linear elasticity, the displacement field u_z =Bϑ r (in cylindrical coordinates r, ϑ, z) was derived. This displacement has a jump on the half-plane ϑ = 0. Stresses orthogonal to this discontinuity plane are continuous.